Disadvantages of Facebook on the family institution and it’s guidelines from Maqasidic approach - Mahmud, Mek Wok; Bux, Siti Nurasila; Bux, Sheikh Johari (2018)
The emergence of social networking sites, most notably Facebook has phenomenal in this postmodern era. The nature of this networking which allows connection to society at large, has affected all levels of society not excluding Muslim family institutions. Although the existence of such sites carries with it number of advantages, the drawbacks this social network is causing should not be overlooked. Islam as a comprehensive religion provides guidance for all aspects of life including utilizing modern technology. This paper aim is to define the benefits and harms (maslahah and mafsadah) of Facebook in relation to family institution and identify solutions from maqasidic perspective. Through qualitative method, data and information gained, the data will be further analyzed through critical reasoning of current related issues weighed from the perspective of Maqāsid Al-Sharī'ah. In addition, the research proposes some Sharī'ah guidelines on Facebook. Ultimately, the finding proves is that Facebook brings more harm to family institutions than benefits. Based on that, the study proposes to Muslims ways to conform with Maqasid al-Sharfah, in order to attain prosperity in this worldly life and the hereafter.